Prevalence of respiratory abnormalities and spirometric disparities among construction workers in Tangail, Bangladesh - Mogal, M. R.; Islam, M. D.; Hasan, M. I.; Akter, Aklima; Mahmod, M. R.; Sompa, Sagarika A.; Junayed, Asadullah; Abedin, M. Z.; Zubair, M. A.; Khatun, Marina; Sikder, M. A. (International Journal Of Community Medicine And Public Health, 2020)
Background: Occupational exposure is a significant factor for having respiratory symptoms and impairment of lung function in the working population. Construction workers impose a great risk of respiratory diseases since they continuously expose to construction hazards at their working place. The objective of this study was to explore the status of respiratory health of construction workers as well as correlation of blood parameters with it. Methods: This cross-sectional study was conducted among construction workers along with the control group (university staffs) by randomly selecting 50 individuals in each group from September 2019 to February 2020 in Tangail, Bangladesh. Questionaries’ survey was executed followed by spirometry and oximetry. After confirming abnormalities of lung function, blood was drawn for further IgE, ESR, and CRP analysis. Results: Significantly (p<0.05) higher percentage of respiratory symptoms such as dyspnea (24%), coughing (30%), sneezing (40%), discomfort of chest (18%) were found in construction workers. In addition, lung function (FVC, FEV1, FEV1%, PEF, PEF%, FEF25, and FEF2575) was significantly (p<0.05) lower in construction workers compared with control. Furthermore, both IgE (353.57±25.41) and ESR (17.87±5.25) also reported a marked rise in the number of construction workers (p<0.05). Conclusions: It can be concluded from our study that construction hazards might the cause of prevalent respiratory symptoms, decreased lung function, and increased inflammatory markers such as IgE and ESR.